Unequal higher education : wealth, status and student opportunity - Taylor, Barrett Jay; Cantwell, Brendan, 1980- (American campus., 2019)
"American higher education is often understood as a vehicle for social advancement. However, the institutions at which students enroll differ widely from one another. Some enjoy tremendous endowment savings and/or collect resources via research, which then offsets the funds that students contribute. Other institutions rely heavily on student tuition payments. These schools may struggle to remain solvent, and their students often bear the lion's share of educational costs. Unequal Higher Education identifies and explains the sources of stratification that differentiate colleges and universities in the United States. Barrett J. Taylor and Brendan Cantwell use quantitative analysis to map the contours of this system. They then explain the mechanisms that sustain it and illustrate the ways in which rising institutional inequality has limited individual opportunity, especially for students of color and low-income individuals₍"--